3. An Immunohistochemical Study of Alpha Estrogen Receptor (ERα) Development in Ovary and Uterus of Rat (Rattus norvegicus) - Sri Wahyuni; Chintya Desfariza; Hamny Hamny; Muslim Akmal; Gholib Gholib; T. Armansyah (Universitas Syiah Kuala, 2019)
This research aimed to observe and identify the development of estrogen receptor alpha (ERα) in the ovary and uterus of rats (Rattus norvegicus) at various age levels using immunohistochemistry (IHC). The ovary and uterus were collected from eight female rats aged 2, 4, 6, and 12 months and processed histologically and stained with IHC staining. This research showed, the intensity of ERα expression was found in high abundance (+++) in stroma and the corpus luteum and was weakly found (+) in the theca cells, blood vessels, oocytes and germinal epithelium of rats aged 2 months. Additionally, ERα expression in rats aged 4 months had similarities with rats aged 2 months, but the intensity of ERα had increased (++) in ovarian theca cells, blood vessels, and oocytes. In ovaries of rats aged 6 and 12 months, ERα expression had decreased (++) in the stroma and the corpus luteum and had a low expression (+) in the blood vessel and oocytes. The uterus of rats aged 2 months had low expression of ERα (+) in the stroma and luminal epithelium, moderate (++) in the myometrium, but was not found in the uterine glands. Furthermore, the expression in the uterus of rats at the age of 4 months had increased in the stroma and luminal epithelium (++) and uterine glands (+). At the age of 6 months, it found excessively (+++) in the stroma, myometrium, and luminal epithelium, moderate expression (++) in the uterine glands. The expression of ERα in uterus aged 12 months was almost equal to the uterus of rats aged 6 months, but the expression in the myometrium and epithelial luminal had decreased (++). It can be concluded that the development and distribution pattern of ERα in the ovaries and uterus of rats are different at each age levels, it may be related to the growth and development of reproductive organs and also closely related to the estrus cycles of rats.